Food allergies and Living with Risk: Navigating everyday life at university when at risk of anaphylaxis - Megan Haslam (The Journal for Undergraduate Ethnography)
Life-threatening food allergies which put an individual at risk of anaphylaxis change the way that everyday life, and the spaces that constitute it, are experienced. Some research within geography has explored children’s experiences of living with this risk, but few until now have explored the complexities of navigating life with a food allergy for young people at university. This research therefore seeks to address this gap by bringing to the fore the experiences of young people who have attended or currently attend university in the UK and live with a life-threatening food allergy. It reveals how their everyday lives and transition to university are made more complex by anaphylaxis risk. These ideas were explored via seven online in-depth, semi-structured interviews with current or recent university students who carry EpiPens and are at risk of anaphylaxis. Through a process of thematic coding, the spatial and relational dimensions of anaphylaxis risk were revealed within different university contexts. An exploration of the impacts of the COVID-19 pandemic on allergy management is also explored as a novel focus. The research calls for more attention to be paid to young people and students at risk of anaphylaxis and the mental health implications of living with allergies.